Real-time lost circulation estimation and mitigation - Abo Taleb T. Al-Hameedi; Husam H. Alkinani; Shari Dunn-Norman; Ralph E. Flori; Steven A. Hilgedick (Egyptian Journal of Petroleum)
Lost circulation is a challenging problem particularly in the Dammam formation of the Rumaila field, Iraq. Drilling engineers are challenged to select the optimum value for key drilling parameters such as equivalent circulation density (ECD), yield point (Yp), mud weight (MW), weight on bit (WOB), rate of penetration (ROP) and revelation per minute (RPM) to mitigate mud losses in this formation. Many of these drilling parameters are inter-related and the overall impact of changing key parameters requires extensive drilling experience or study.A multi-regression analysis was performed on mud loss event data for more than 300 wells drilled in the Dammam formation. From this analysis, a model was developed to predict the total mud losses. Mud loss was found to be significantly affected by MW, ECD, and ROP. Models for these key parameters were also developed from the multi-regression analysis. The models were confirmed with additional well data from new wells drilled in the field. The models developed in this work provides a method for setting predicted mud losses, then limiting the operational drilling parameters to mitigate such losses in the future wells in fields with similar lithology.Proactive approaches are made prior to entering the Dammam formation to prevent or mitigate the occurrence of the lost circulation. Key drilling parameters are estimated to use during drilling through this formation. In case preventive measures didn’t work, corrective actions are determined for each type of mud losses to provide effective remedies, minimize non-productive time, and reduce cost. The best lost circulation strategy to the Dammam formation is concluded and summarized depending on a comprehensive statistical work, the most important courses of the international oil companies, technical papers, textbooks, and economic evaluation to determine the successful remedies for each type of losses. These treatments are classified by relying on the mud losses classifications to avoid unwanted consequences due to inappropriate actions. Keywords: Lost circulation, Drilling fluid, Mud losses prediction, Dammam formation, Iraq